Gestational exposure to titanium dioxide, diesel exhaust, and concentrated urban air particles affects levels of specialized pro-resolving mediators in response to allergen in asthma-susceptible neonate lungs. Issue 6 (19th March 2022) - Kumar, Mohan; Yano, Naohiro; Fedulov, Alexey V.
ABSTRACT: Maternal gestational exposures to traffic and urban air pollutant particulates have been linked to increased risk and/or worsening asthma in children; however, mechanisms underlying this vertical transmission are not entirely understood. It was postulated that gestational particle exposure might affect the ability to elicit specialized proresolving mediator (SPM) responses upon allergen encounter in neonates. Lipidomic profiling of 50 SPMs was performed in lungs of neonates born to mice exposed to concentrated urban air particles (CAP), diesel exhaust particles (DEP), or less immunotoxic titanium dioxide particles (TiO2). While asthma-like phenotypes were induced with identical eosinophilia intensity across neonates of all particle-exposed mothers, levels of LXA4, HEPE and HETE isoforms, and HDoHe were only decreased by CAP and DEP only but not by TiO2. However, RvE2 and RvD1 were inhibited by all particles. In contrast, isomers of Maresin1 and Protectin D1 were variably elevated by CAP and DEP, whereas Protectin DX, PGE2, and TxB2 were increased in all groups. Only Protectin D1/DX, MaR1(n-3, DPA), 5(S), 15(S)-DiHETE, PGE2, and RvE3 correlated with eosinophilia but the majority of other analytes, elevated or inhibited, showed no marked correlation with inflammation intensity. Evidence indicates that gestational particle exposure leads to both particle-specific and nonspecific effects on the SPM network.